2007
DOI: 10.1016/j.preteyeres.2007.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic mechanisms of gene regulation during lens development

Abstract: Recent studies demonstrated a number of links between chromatin structure, gene expression, extracellular signaling and cellular differentiation during lens development. Lens progenitor cells originate from a pool of common progenitor cells, the pre-placodal region (PPR) which is formed due to a complex exchange of extracellular signals between the neural plate, naïve ectoderm and mesendoderm. A specific commitment to the lens program over alternate choices such as the formation of olfactory epithelium or the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
125
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(127 citation statements)
references
References 365 publications
(468 reference statements)
1
125
0
1
Order By: Relevance
“…Lens fiber cell differentiation is characterized by the temporal and spatially restricted expression of crystallin genes (Cvekl and Duncan, 2007). Our data showed that loss of MAPK1 did not affect crystallin gene expression (Fig.…”
Section: Fig 5 Fiber Cell Differentiation (Ab) P57mentioning
confidence: 54%
“…Lens fiber cell differentiation is characterized by the temporal and spatially restricted expression of crystallin genes (Cvekl and Duncan, 2007). Our data showed that loss of MAPK1 did not affect crystallin gene expression (Fig.…”
Section: Fig 5 Fiber Cell Differentiation (Ab) P57mentioning
confidence: 54%
“…lens, retina, cornea, iris, olfactory epithelium, forebrain, cerebellum, and pancreas) (41,43,44,79). It has been shown that Pax6 regulates the batteries of common target genes in distinct tissues, including the lens and neurons (57,80).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in contrast to the majority of sequencespecific DNA binding proteins that use a single DNA-binding domain that typically docks with 6 -10 bp of DNA, Pax6 can use ␤-sheets, PAI, linker, RED, and HD, and their various combinations to bind DNA. Although some important direct targets of Pax6 genes have been identified (41), a large body of work remains to be accomplished (42)(43)(44). Some transcription factors, especially those with multiple DNA-binding subdomains (e.g.…”
mentioning
confidence: 99%
“…Pax6 is known to bind, activate and repress crystallin gene expression in vitro and in vivo during early stages of development (Cvekl and Duncan, 2007;Cvekl et al, 2004). During the late stages of newt lens regeneration, which emulates normal lens development, Pax6 has been shown to be needed for LFC differentiation but not for crystallin maintenance (Madhavan et al, 2006).…”
Section: Research Articlementioning
confidence: 99%
“…Other proposed mechanisms include direct association of Pax6 with the centrosomes or mitotic chromosomes in proliferating cortical progenitors and cultured cells, respectively (Tamai et al, 2007;Zaccarini et al, 2007). The relevance of the above findings to Pax6 function in cell cycle regulation in the lens remains to be investigated.Pax6 is known to bind, activate and repress crystallin gene expression in vitro and in vivo during early stages of development (Cvekl and Duncan, 2007;Cvekl et al, 2004). During the late stages of newt lens regeneration, which emulates normal lens development, Pax6 has been shown to be needed for LFC differentiation but not for crystallin maintenance (Madhavan et al, 2006).…”
mentioning
confidence: 99%